2013
DOI: 10.1111/iju.12232
|View full text |Cite
|
Sign up to set email alerts
|

Standardized assessment of complications in a contemporary series of European patients undergoing radical cystectomy

Abstract: Abbreviations & AcronymsObjectives: To examine postoperative complications in a contemporary series of patients after radical cystectomy using a standardized reporting system, and to identify readily available preoperative risk factors. Methods: Using the modified Clavien-Dindo classification, we assessed the 90-day postoperative clinical course of 535 bladder cancer patients who underwent radical cystectomy and urinary diversion (ileal conduit n = 349, ileal neobladder n = 186) between June 2003 and February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
54
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 29 publications
8
54
1
4
Order By: Relevance
“…First, we show that the risk of postoperative complications after RC for bladder cancer remains high in a contemporary cohort (up to 30%). This is consistent with complication rates reported in previous studies, 1,2,6,8,20 and corroborates the need for accurate identification of preoperative risk factors for potentially avoidable adverse events. Our results suggest that preoperative BMI represents a significant predictor of overall postoperative complications.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…First, we show that the risk of postoperative complications after RC for bladder cancer remains high in a contemporary cohort (up to 30%). This is consistent with complication rates reported in previous studies, 1,2,6,8,20 and corroborates the need for accurate identification of preoperative risk factors for potentially avoidable adverse events. Our results suggest that preoperative BMI represents a significant predictor of overall postoperative complications.…”
Section: Discussionsupporting
confidence: 91%
“…Our results suggest that preoperative BMI represents a significant predictor of overall postoperative complications. Previous studies have linked increased BMI to a substantially higher risk of wound infection and dehiscence, 2,20 while others have suggested that construction of either urinary diversions or orthotopic bladder substitu- Although we do not advocate that obesity should be considered a contraindication for surgery, these patients may do better in the care of an experienced urologist. Additionally, modifying surgical technique and using the appropriate surgical instruments are essential to minimizing the risk of adverse short-term outcomes in obese patients.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations